Assessing the Efficacy of a Justice-Mental Health Collaborative Program to Reduce Violence - Atkin-Plunk, Cassandra A. (American journal of criminal justice, 2025)
In the aftermath of tragic mass violence events, there has been increasing attention to strategies for improving police responses to mental health crises and the risk of violence. In light of these concerns, this study comprises an evaluation of the Linking Individuals in Need of Care (LINC) Program—a collaborative initiative involving a sheriff’s office and behavioral health network in a large Florida county. Implemented as part of the Bureau of Justice Assistance funded Justice and Mental Health Collaborative Program, the LINC Program aims to identify and support at-risk individuals, with an emphasis on preventing school and community mass violence incidents. This study evaluates the program’s processes in identifying these individuals, examines protocols for intervention, identifies implementation factors, and assesses the program’s impact on reducing the risk of violence. The study also makes recommendations for future study and evidence-based practices in policing and mental health partnerships.